2006
DOI: 10.1109/jsen.2006.878001
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel Multiplexed Temperature Sensor System Using Bragg-Grating-Based Fiber Lasers

Abstract: A parallel multiplexed temperature sensor scheme using a Bragg grating-based fiber laser approach has been developed and evaluated. Multiple laser cavities were formed as the active gain media of the system using a common broadband chirped fiber Bragg grating (CFBG) and several normal FBGs, which were used as optical feedback elements, in conjunction with different lengths of erbium-doped fibers (EDFs). These gain media were externally pumped by light from a 1480-nm laser diode (LD) through a 1480-nm 1 × 4 spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Mandal et al have reported multiplexed temperature sensor systems by using an optical fiber FBG sensor over the range from 27 • C to 540 • C [15]. He have reported that FBGs-based temperature sensing using a femtosecond laser operates up to 1000 • C [16].…”
Section: Introductionmentioning
confidence: 99%
“…Mandal et al have reported multiplexed temperature sensor systems by using an optical fiber FBG sensor over the range from 27 • C to 540 • C [15]. He have reported that FBGs-based temperature sensing using a femtosecond laser operates up to 1000 • C [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the previous approaches have been proposed to suppress the MLM spikes for stable SLM operation, including utilization of the saturable absorber (SA) based filter, phase-shifted fiber Bragg grating (FBG), ultra-narrow optical filter, compound-fiber-ring method, optical injection technique and Rayleigh backscattering (RB) characteristic, respectively [8][9][10][11][12][13]. Furthermore, to obtain the tunability in the EDF lasers, utilization of tunable bandpass filter (TBF), narrow passband filter, variable FBG, silicon-microringresonator (SMR) and Fabry-Perot tunable fiber (FP-TF) have been operated in the fiber ring for wavelength-selection [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Fiber Bragg Grating sensor network analyzer as a new type of sensor is widely used to measure the temperature [1], strain [2], the pressure [6], displacement [10], vibration [7] and so on. There is significant practical value and broad application prospects in the engineering and technical fields of the aerospace, large dam bridges, ships vehicles, tunnel construction, electromagnetic interference, disaster monitoring, intelligent materials, etc.…”
Section: Introductionmentioning
confidence: 99%